2019
DOI: 10.1021/acs.jpclett.8b03222
|View full text |Cite
|
Sign up to set email alerts
|

γ-Ray-Induced Degradation in the Triple-Cation Perovskite Solar Cells

Abstract: We report on the impact of γ radiation (0–500 Gy) on triple-cation Cs0.15MA0.10FA0.75Pb­(Br0.17I0.83)3 perovskite solar cells. A set of experiments was designed to reveal the individual contributions of the hole-collecting bottom electrode, perovskite absorber, and electron transport layer (ETL) to the overall solar cell degradation under radiation exposure. We show that the glass/ITO/PEDOT:PSS hole-collecting electrode withstands a 500 Gy dose without any losses in the solar cell performance. In contrast, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…The same behaviour was also observed for PVMX samples. The sensitivity of pure- [ 29 ] and mixed-halide perovskites [ 30 ] to visible and even radiation [ 31 ] has been often reported. In mixed halides, perovskite photo-excitation was proven to determine a reversible phase separation into iodine-rich and bromide-rich domains [ 30 ], recently attributed to the local strain generated by the interaction of the photo-excited charges with the ionic lattice [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same behaviour was also observed for PVMX samples. The sensitivity of pure- [ 29 ] and mixed-halide perovskites [ 30 ] to visible and even radiation [ 31 ] has been often reported. In mixed halides, perovskite photo-excitation was proven to determine a reversible phase separation into iodine-rich and bromide-rich domains [ 30 ], recently attributed to the local strain generated by the interaction of the photo-excited charges with the ionic lattice [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The importance of efficiency, weight and size have made PVKs a promising prospect for space applications, and as such there is are efforts to analyse the tolerance of these materials to radiation. Gamma-ray studies have shown small losses in J sc in mixed-halide systems, due to radiation-induced phase segregation, 92 similar to the Hoke effect, 93 although the largest losses are due to colour centers in the glass reducing transmittance. 94 The broad quantum efficiency of most photodetectors used in combination with scintillators makes precise tuning of the band gap by alloying different halides less important than in solar cells; as a result this phase segregation should not impact PVK indirect detectors.…”
Section: Pvk Scintillator Performancementioning
confidence: 99%
“…Due to 100–1000 Gy represents a typical stability benchmark for satellites working at low and middle equatorial orbits, [ 76 ] gamma ray radiation of 150, 300, and 500 Gy doses were applied to the Cs 0.15 MA 0.10 FA 0.75 Pb(Br 0.17 I 0.83 ) 3 perovskite absorber material, electron transporting material (PC 61 BM), hole transporting materials (PEDOT:PSS) and ITO glass substrate. [ 77 ] It was shown that the dose up to 500 Gy did not damage the PEDOT:PSS layer, however, radiation affected the performance of the PC 61 BM layers significantly. Also, the radiation tolerance of regular PSCs with a structure of glass/ITO/SnO 2 /Perovskite/Spiro‐OMeTAD/Ag under gamma rays with dose rate of 100, 200, and 500 krad s −1 were investigated.…”
Section: Radiation Resistance Of Perovskite Solar Cellsmentioning
confidence: 99%